Proyecto de inversión para la comercialización de isalgén en el Ecuador - Escudero Jurado, Xavier Virgilio (2009)
The aim of this investigation is to look for ways of positioning on the Ecuadoran market the anti-spasmodic Isalgen, whose principal competitor is Buscapina. It is going to be achieved to introduce the product on the potential market, to then position the same one in the mind of the objective consumer, demonstrating this way the excellent thing that is the product and to take care of the health of the persons avoiding retwists, abdominal colic, Since this one relates basically to the spasm produced by the muscular smooth fibers of the alimentary or urinary canal as consequence of some obstructive, infectious, inflammatory process, irritative or for I accumulate of gases. In agreement to realized studies there is going to be obtained an increasing and wide participation of market, such that in the long term the product is a leader of the target and like that market to achieve a loyalty on the part of the client put towards the product. It will be achieved to reach an increase in the sales of the product in 5 % per year. One will use the pharmaceutical existing literature to determine the precedents of the raised problem.